1971
DOI: 10.1111/j.1432-1033.1971.tb01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthese de la chaine lateale ethyle du stigmastanol et du stigmasten-22,ol-3beta du myxomycete Dictyostelium discoideum

Abstract: (Repu le 7 mai/l2 octobre 1971) Several laboratories have shown that the two carbon atoms C-28 and C-29 of the ethyl or ethylidene side chains of phytosterols are introduced on to a C-24 unsaturated side chain by two methylation steps. A scheme based on previous work suggests the various intermediates which can be formed by stabilisation of the carbonium ion 3. We have shown previously that in the biosynthesis of 50i-stigmastan-3p-01 ( l l a ) and 5a-stigmast-22-en-3/3-01 (12a), sterols of the myxomycete Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…2). ated compounds (data not shown) as shown by Lederer and :yclolaudenol in coworkers (27,28). The mechanism of C-24 alkylation pery mechanism b formed by D. discoideum is therefore mechanism a or the one or mechanism b following the A24 (28) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2). ated compounds (data not shown) as shown by Lederer and :yclolaudenol in coworkers (27,28). The mechanism of C-24 alkylation pery mechanism b formed by D. discoideum is therefore mechanism a or the one or mechanism b following the A24 (28) …”
Section: Resultsmentioning
confidence: 99%
“…The GLC chromatogram of the ethereal extract of saponified cells indicated that several [not just two as previously thought (26)(27)(28)] compounds may be steroidal (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…discoideum (12,15). In addition, approximately 5% of the sterol content had a retention time characteristic of stigasmanol, which has been shown to be a minor sterol constituent in D. discoideum (7). The remaining sterol component, 5 to 10o of the total, has yet to be identified.…”
Section: Resultsmentioning
confidence: 99%